Alzheimer’s Disease Diagnosis: Discrepancy between Clinical, Neuroimaging, and Cerebrospinal Fluid Biomarkers Criteria in an Italian Cohort of Geriatric Outpatients: A Retrospective Cross-sectional Study - Dolci, Giulia A. M.; Damanti, Sarah; Scortichini, Valeria; Galli, Alessandro; Rossi, Paolo D.; Abbate, Carlo; Arosio, Beatrice; Mari, Daniela; Arighi, Andrea; Fumagalli, Giorgio G.; Scarpini, Elio; Inglese, Silvia; et al. (Frontiers in Medicine, 2017)
Background: The role of cerebrospinal fluid (CSF) biomarkers and neuroimaging in the diagnostic process of Alzheimer Disease (AD) is not clear, in particular in the older patients. Objective: To compared the clinical diagnosis of AD with CSF biomarkers and with cerebrovascular damage at neuroimaging in a cohort of geriatric patients Methods: Retrospective analysis of medical records of ≥65 year old patients with cognitive impairment referred to an Italian geriatric outpatient clinic, for whom the CSF concentration of Aβ, Tau and p-Tau was available. Clinical diagnosis (no dementia, possible and probable AD) was based on the following two sets of criteria: i) the Diagnostic Statistical Manual of mental disorders (DSM-IV) and of the National Institute of Neurological and Communicative Disorders and Stroke and the Alzheimer's Disease and Related Disorders Association (NINCDS-ADRDA); and ii) the National Institute on Aging –Alzheimer's Association (NIA-AA). The Fazekas visual scale was applied when a Magnetic Resonance Imaging scan was available. Results: We included 94 patients, mean age 77.7, mean MMSE score 23.9. The concordance (kappa coefficient) between the two sets of clinical criteria was 70%. Mean CSF concentration [pg/ml] (± standard deviation) of biomarkers was: Aβ 687 (± 318), Tau 492 (± 515), and p-Tau 63 (±56). There was a trend for lower Aβ and higher Tau levels from the no dementia to the probable AD group. The percentage of abnormal liquor according to the local cut-offs was still 15% and 21% in patients without AD based on the DSM-IV plus NINCDS-ADRDA or the NIA-AA criteria, respectively. The exclusion of patient in whom normotensive hydrocephalus was suspected did not change these findings. 80% of patients had the neuroimaging report describing chronic cerebrovascular damage, while the Fazekas scale was positive in 45% of patients overall, in 1/2 of no dementia or possible AD patients, and in about 1/3 of probable AD patients, with no difference across ages. Conclusions: We confirmed the expected discrepancy between different approaches to the diagnosis of AD in a geriatric cohort of patients with cognitive impairment. Further research is needed to understand how to interpret this discrepancy and provide clinicians with practical guidelines.